Efisiensi Serapan Hara dan Hasil Padi pada Budidaya SRI di Persawahan Pasang Surut dengan Menggunakan Kompos Diperkaya - Razie, Fakhrur; Anas, Iswandi; Sutandi, Atang; Sugiyanta, ,; Gunarto, Lukman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
There are two main problems when system of rice intensification (SRI) cultivation is carried out at tidal areas, e.g. the presence of Fe which is potentially toxic to plants and low nutrients availability. Utilization of Azotobacter-enriched compost is a choice to overcome iron toxicity as well a source of nutrients. The aims of this research were to study the effect of Azotobacter enriched compost to reduce the rates of inorganic fertilizers applied, to increase the efficiency of N, P, and K uptake, and to increase plant growth and yield. Two rice cultivation methods were applied namely SRI and conventional rice cultivation methods on tidal lands (rice fields) of South Kalimantan. A completely randomized block design with two factors was applied. The main plots were SRI and conventional rice cultivation, and as subplots were eight types of fertilizer that is a combination between Azotobacter-enriched compost with inorganic fertilizers rates. The results showed that soil nutrient availability, uptake and efficiency of N, P, and K with SRI technique was higher than conventional cultivation. Azotobacter- enriched compost on the tidal land (rice fields) could reduce the use of N and K fertilizer by 25%. Furthermore, the efficiency of N and P uptake in enriched compost with 75% of fertilizer N, P, and K were not different with enriched compost with 75% of fertilizer. Ciherang rice yields with SRI cultivation was approximately 22% higher compared to that from conventional rice cultivation. Keywords: Azotobacter-enriched compost, conventional rice cultivation, inorganic fertizers